Messages of Personal Identity Attempt in Foreign Criminal Rules - Fenyvesi, Csaba (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2024)
Research worldwide and in our country (Hungary) have revealed that false personal identities play a prominent role in “justizmord” cases. That is why it is worthwhile having a closer look at identity rules and methodologies of other countries in this respect as well. In this study, the author examines the Slovenian, Austrian, Swiss, Serbian, Croatian, and distant (but, as it turns out, much the same) Turkish norms, all embedded in the continental legal system just like the Hungarian ones. Based on the legal details and implementation recommendations there, the researcher formulates at the end of his study the lessons learned from the models, the legal and forensic development opportunities available to us, the conclusions for efficiency and fairness, and the current and future messages to legislators and practitioners.